Social inclusion programmes and inclusive growth in developing countries (UN New YorkUS, 2014)
Examines why recent growth in developing countries has not been inclusive and discusses what is needed to move towards more inclusive growth and development pathways. Highlights and discusses selected social inclusion programmes that have been put in place in some developing countries and draws lessons from these programmes for other developing countries.
Keywords: SOCIAL INTEGRATION